2017
DOI: 10.1038/s41598-017-08722-3
|View full text |Cite
|
Sign up to set email alerts
|

Neuroinflammation alters cellular proteostasis by producing endoplasmic reticulum stress, autophagy activation and disrupting ERAD activation

Abstract: Proteostasis alteration and neuroinflammation are typical features of normal aging. We have previously shown that neuroinflammation alters cellular proteostasis through immunoproteasome induction, leading to a transient decrease of proteasome activity. Here, we further investigated the role of acute lipopolysaccharide (LPS)-induced hippocampal neuroinflammation in cellular proteostasis. In particular, we focused on macroautophagy (hereinafter called autophagy) and endoplasmic reticulum-associated protein degra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 40 publications
(58 reference statements)
1
19
0
Order By: Relevance
“…Hence, it is not surprising that recent research has brought the role of UPR in neuroinflammation into focus as a converging pathological pathway. Indeed, recent work has highlighted the existence of a one-directional cause-and-effect relationship between activation of the UPR due to proteasome dysfunction and neurodegeneration (83)(84)(85). Here, our results support a role for the UPR in triggering neuroinflammation, which is a key component of neurodegenerative diseases.…”
Section: Discussionsupporting
confidence: 84%
“…Hence, it is not surprising that recent research has brought the role of UPR in neuroinflammation into focus as a converging pathological pathway. Indeed, recent work has highlighted the existence of a one-directional cause-and-effect relationship between activation of the UPR due to proteasome dysfunction and neurodegeneration (83)(84)(85). Here, our results support a role for the UPR in triggering neuroinflammation, which is a key component of neurodegenerative diseases.…”
Section: Discussionsupporting
confidence: 84%
“…2a). Proteasomal function can be compromised by the neuroinflammation which often accompanies neurodegeneration [32, 4144], and as Sho has a nucleic acid–binding region [29] suggestive of a role in molecular pattern recognition after infections, we also tested the effects of two innate immune ligands. Although glycosylated Sho levels were mildly decreased by these treatments ( p = 0.0295 for poly I:C), unlike the effect of proteasomal inhibitors, we were unable to detect a commensurate increase in level for the unglycosylated forms of Sho (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These lines of evidence highlight a possibility that autophagy serves as the common machinery in regulating microglia-mediated inflammation in response to a multitude of inflammatory stimuli. Yet, another study demonstrated that LPS injection induced autophagy activation in rat hippocampus ( Pintado et al, 2017 ). Autophagy is a catabolic process that can be activated during starvation, stress and nutrient deprivation by different signaling pathways.…”
Section: Discussionmentioning
confidence: 99%